#MeToo dans l’édition : tout le monde savait - Un collectif de plus de 100 personnalités de l'édition (Libération, 2021)
Plus d’une centaine de femmes travaillant dans le livre signent un texte dénonçant un climat délétère et des inégalités flagrantes. Elles demandent que les entreprises de l’édition prennent leur responsabilité.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; europe; france; inégalités; metoo; patriarcat; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles

Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

How far the ecowarrior will go: An ecofeminist reading of disney's Moana - Hernawati, Mala (3L: Language, Linguistics, Literature, 2021)
This article attempts to look into the fictional narrativization of women's significant and distinctive relationship with nature in Disney's Moana. Emphasizing the power and the unity of women and nature in Polynesian indigenous culture, Moana suggests that the destruction of nature results from exploitative and manipulative masculinity. Through ecofeminist perspectives, this essay observes that Moana offers critical views and promotes awareness of gender and environmental issues. These ideas are communicated through the visual and verbal depiction of power relations that defy patriarchal tradition alongside the expressions of protest against devaluation and abuse of nature and women. To put it in the context of the development of themes in Disney's princess line, Moana's presence can be a novel alternative to the typical images of women, namely a new portrayal of a female character whose primary concern is not romance but instead the sustainability of the environment where she lives. This study also confirms that Disney's animated princess films continuously adjust with the dynamics of global feminist discourse. © 2021 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; capitalisme; environnement; film d'animation; féminisme pop; histoire et politique; patriarcat; princesse disney; projet charge mentale; périodes historiques; systèmes d'oppressions; thématiques; écoféminisme

Patriarcavirus, feminist dystopias and COVID-19: Reflections on the phenomenon of gender pandemics - Machado-Jiménez, Almudena (Feminismo/s, 2021)
This essay examines contemporary feminist dystopias to study the phenomenon of gender pandemics. Gender pandemic narrative allegorises possible aftermaths of patriarcavirus, unleashing many natural disasters that force global biopolitics to hinder gender equality. The main objective of this essay is to explain how gender pandemics are appropriated in patriarchal utopian discourses as a pretext to control female empowerment, diagnosing women as diseased organisms that risk the state’s well-being. Moreover, the novels explore the interdependence between biology and sociality, portraying the acute vulnerability of female bodies during and after the pandemic conflicts, inasmuch as patriarchal power arranges a hierarchical value system of living that reinforces gender discrimination. Particularly, the COVID-19 emergency is analysed as a gender pandemic: the exacerbated machismo and the growing distress in the female population prove that women are afflicted with a suffocating patriarcavirus, which has critically gagged them in the first year of the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; arts; corps; covid-19; discipline; droits des femmes*; genre; patriarcat; précarité; périodes historiques; ressource en ligne; santé; systèmes d'oppressions; thématiques; violences; études littéraires

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

« La propriété d’une maison pavillonnaire dans l’imaginaire de la famille et les conditions économiques des familles avec enfants » dans Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales - Pugliese, Maude (Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales, 2021)
"La réalisation des projets de couple et familiaux constitue des préoccupations importantes des individus contemporains. Ces projets font l'objet de représentations sociales générées par diverses sources?: œuvres littéraires, philosophiques, scientifiques, populaires, mais aussi cinématographiques ou médiatiques. Ces représentations proposent des modèles et fournissent des supports à des imaginaires alimentant les scénarios personnels, créant des attentes qui se heurtent aux réalités quotidiennes, et qui entrainent souvent des désillusions et des déceptions, mais aussi des adaptations. Dans le but de mieux saisir les logiques à l'œuvre dans les attentes conjugales et familiales, cet ouvrage composé de treize chapitres rédigés par des chercheuses et chercheurs québécois, canadiens et internationaux (Brésil, Espagne, France, Suisse), issus de disciplines variées (anthropologie, démographie, psychologie, sexologie, sociologie et travail social), vise à mettre en évidence l'influence des imaginaires sur les itinéraires conjugaux et familiaux. La richesse des contributions à cet ouvrage collectif devrait aider à mieux saisir l'importance des études sur les imaginaires familiaux, autant pour la communauté scientifique que pour toute personne intéressée à mieux comprendre, et possiblement à mieux accompagner, les imaginaires, les attentes et les désillusions conjugales et familiales vécues par les individus et les couples."
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; europe; famille; inégalités; maternité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Examining the cracks in universal water coverage: Women document the burdens of household water insecurity - Radonic, Lucero; Jacob, Cara E. (Water Alternatives, 2021)
L’accès universel à l’eau potable est considéré comme une caractéristique déterminante des villes du Nord global. Cet article décrit les défis quotidiens auxquels sont confrontées les femmes de la classe ouvrière de Flint, dans le Michigan, lorsque la promesse d’une infrastructure d’eau moderne se fissure. En 2014, afin de réduire les coûts, la source d’eau potable de Flint a été transférée du lac Huron à la rivière Flint. Ce changement, et plus particulièrement la manière dont il a été géré, a entraîné une contamination de l’approvisionnement en eau par du plomb et des agents pathogènes. Si l’expérience de Flint est désormais un cas emblématique d’insécurité hydrique dans le Nord global, elle n’est pas unique. À travers une étude de cas élaborée dans le cadre d’un projet de recherche participative communautaire, cet article détaille comment l’insécurité hydrique a transféré la charge de l’approvisionnement en eau potable aux ménages individuels, et plus particulièrement aux femmes. Plutôt que de pouvoir compter sur la main-d’œuvre et l’expertise technique qui ont rendu l’eau potable dans la ville moderne, les habitants de Flint ont été soudainement rendus responsables de la sécurité de leur propre approvisionnement en eau. Nous expliquons comment la crise de l’eau de Flint a fait naître une « nouvelle normalité » ; Nous examinons les façons dont cette situation a donné naissance à un nouveau rapport à l'eau potable, caractérisé par un (re)retour à l'eau en bouteille ou filtrée (de l'eau du robinet) et par un changement dans la répartition des tâches nécessaires à la production d'eau potable. Les témoignages de femmes que nous présentons ici illustrent comment, lorsque l'eau uniforme moderne fait défaut, les gens commencent à voir des eaux hétérogènes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; accès à l'eau potable; amériques; anthropologie; approches et analyses; capitalisme; discipline; eau en bouteille; environnement; histoire et politique; inégalités hommes-femmes; patriarcat; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences